Study Of Sustainable Economic Growth Through Strengthening Digitalpreneur and Creativepreneur in Msme Actors in Kota Pari Village - Rizky, M Chaerul; Ardian, Noni; Putra, Nusa Ekasyah; Santika, Eva (Journal of Community Research and Service, 2023)
This study's objective was to identify and analyze sustainable economic growth through the strengthening of digitalpreneurs and creativepreneurs for MSME actors in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Province. In addition, economic growth is the process of changing a nation's economic conditions in a sustainable fashion towards a more prosperous state for all its citizens over time. In an effort to increase economic growth, the government has promoted the spirit and spirit of entrepreneurship, particularly becoming a digitalpreneur, which is part of entrepreneurship based on the large number of internet users in Indonesia, especially mobile internet, in the hope that digitalpreneurs can become a potential new pillar of the national economy that grows and develops from the creative-preneur spirit of the nation's generation in developing businesse. The method employed is a quantitative descriptive method, namely the study of literature, theory, or literature in order to provide an overview of certain facets of the examined population's way of life. The research sample included 30 respondents who were involved with MSMEs. The results of the study indicate that digitalpreneurs and creativepreneurs have a positive and significant impact on sustainable economic growth.